One World - Mitchner, Alyn E and Tuffs, Joanne (Reidmore Books Inc, 1989)
We live in a global environment.The realities of the earth's natural forces,in combination with human made influences,establish the limits of our lifestyle.
Keywords: Juvenile literature- Non-Fiction